Factores que afectan al rendimiento en carreras de fondo - Ogueta-Alday, A.; Garcia-Lopez, J. (Revista Internacional de Ciencias del Deporte, 2016)
The number of competitions and participation on long-distance races (from 5 km to the marathon) in Spain has grown significantly during the last few years. Due to this popularity, both coaches and runners are interested on learning about the factors that affect long-distance running performance. Facing this new reality, scientific literature has been concerned about the aforementioned factors, and the amount of studies has considerably grown. Therefore, the purpose of this review is to analyse factors affecting long-distance running performance from different points of view. Literature review was performed through 3 different databases (Medline, SportDiscus and Google Scholar) and the factors were classified into 5 main groups, subdivided into different sections: 1- environmental (air/wind, temperature, humidity, altitude and slope of the ground), 2- training-related (endurance, resistance, training in hot environments and in altitude), 3- physiological (VO2max, thersholds, running economy, age, gender, muscle fibre type, fatigue and race), 4- biomechanical (anthropometry, leg-stiffness, flexibility, foot strike pattern, footwear, foot orthoses and spatio-temporal parameters) and 5- psychological (intervention strategies, direction of attention and music). Even though the influence of some of these factors on running performance in quite well-known, the influence of some psychological (direction of attention and music) and biomechanical factors (foot strike pattern and spatio-temporal parameters) is still unclear. There are few studies or the results cannot be generalized. Future studies and the progress of new technologies and measurement tools will provide a better understanding.